‘Once Upon a Megalithic Time…’: the Representation of Archaeology in Irish Tourism Literature - Sarah McCarthy (Papers from the Institute of Archaeology, 2002)
This paper is drawn from postgraduate research which looked at the role and representation of archaeology in Irish heritage tourism. At issue is how archaeology and archaeological sites are represented in brochures and ‘flyers’ which have been produced in Ireland for the tourist market. The discussion centres on the relationship this representation may have with issues of Irish identity and the conservation, management and use of archaeology in modern Ireland. The portrayal of Ireland, both at home and abroad, has long been dominated by tourism images. In turn, prevalent within and among these images are archaeological monuments and artefacts, whose primary role seems largely to support a particular understanding of the Irish past (and present). Parallels are drawn between the language and imagery employed in the brochures, and that of 19th century Irish nationalism. Whilst archaeology’s pivotal position in modern Irish heritage tourism is acknowledged, it is argued that the presentation and management of archaeology renders it intangible, static and ‘otherworldly’. This not only pre-empts public engagement with the processes behind the formation of the archaeological record in the past (and present), but facilitates the unquestioned use of archaeology in economic and political spheres.
Keywords: Tourism; Representation; Public archaeology